Cell-derived nanomaterials for biomedical applications - Li Xian Yip; Jinping Wang; Yuling Xue; Kuoran Xing; Cansu Sevencan; Katsuhiko Ariga; David Tai Leong (Science and Technology of Advanced Materials, 2024)
The ever-growing use of nature-derived materials creates exciting opportunities for novel development in various therapeutic biomedical applications. Living cells, serving as the foundation of nanoarchitectonics, exhibit remarkable capabilities that enable the development of bioinspired and biomimetic systems, which will be explored in this review. To understand the foundation of this development, we first revisited the anatomy of cells to explore the characteristics of the building blocks of life that is relevant. Interestingly, animal cells have amazing capabilities due to the inherent functionalities in each specialized cell type. Notably, the versatility of cell membranes allows red blood cells and neutrophils’ membranes to cloak inorganic nanoparticles that would naturally be eliminated by the immune system. This underscores how cell membranes facilitate interactions with the surroundings through recognition, targeting, signalling, exchange, and cargo attachment. The functionality of cell membrane-coated nanoparticles can be tailored and improved by strategically engineering the membrane, selecting from a variety of cell membranes with known distinct inherent properties. On the other hand, plant cells exhibit remarkable capabilities for synthesizing various nanoparticles. They play a role in the synthesis of metal, carbon-based, and polymer nanoparticles, used for applications such as antimicrobials or antioxidants. One of the versatile components in plant cells is found in the photosynthetic system, particularly the thylakoid, and the pigment chlorophyll. While there are challenges in consistently synthesizing these remarkable nanoparticles derived from nature, this exploration begins to unveil the endless possibilities in nanoarchitectonics research.